Sustainable well-being objective indicators: Basic necessities, complementary needs and desired opportunities - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Alias (Springer, 2018)
This study assesses the theories and approaches to sustainable well-being in developing objective social indicators to recognise the all-inclusive wellness of Malaysians. Problem: Currently, in Malaysia, well-being is measured by the Economic Planning Unit (EPU) Malaysia through the Malaysian Quality of Life Reports and Malaysian Well-being Report. The reports cover the social progress of Malaysians through a set of indicators categorised under economic wellbeing and social well-being. The three main issues found in the current approach include (1) a lack of output indicators for some components, which makes it impossible to interpret the true performance of well-being, (2) the absence of a hierarchy of needs to identify more prioritised components and indicators, and (3) a narrow understanding of progress due to a strong reliance on the correlation with GDP growth. Approach: This study employs a literature review and document analysis. Findings: A new approach is necessary to improve the current approach to measuring well-being in Malaysia. Based on the theory of the hierarchy of needs, the objective indicators are categorised into specific components of three dimensions of sustainable well-being – necessities, complementary needs, and desired opportunities. Through reconsideration and re-coordination of the existing indicators and selected additional indicators, the elements that constitute well-being as well as the data appear consistent and transparent. Significance: Sustainable well-being indicators will prioritise what is most important to the citizens. The model recognises the progress of the survival requirements of human beings, the moral basis of happiness, and the greater life prospects of Malaysians.